Evaluasi Ranah Afektif Pembelajaran Pendidikan Agama Islam Dalam Persepektif Kurikulum 2013 - Mufidah, Luk Luk Nur (AL-WIJDÃN Journal of Islamic Education Studies, 2020)
We realize that between the learning process, behavior, human growth and development and how our thoughts and our feelings are interconnected and very influential in decision making. PAI teachers found several problems in carrying out the Affective domain evaluation. This study aims to describe and analyze the planning, implementation and evaluation of the affective domain in SMAN 1 and SMKN 1 Kertosono Nganjuk. This research design uses a multi-site study design, which seeks to describe a particular setting, object or event in detail and in depth. There are similarities and differences in the planning for evaluating PAI learning in the affective domain at SMAN 1 Kertosono Nganjuk and SMKN 1 Kertosono Nganjuk. The equation is an affective domain of PAI learning evaluation planning in the two schools that are both planned and outlined in the RPP. The difference is that in SMAN 1 Kertosono Nganjuk pays more attention to the whole affective domain of the PAI learning evaluation planning procedure. Reporting the evaluation of PAI affective domain learning in SMAN 1 Kertosono Nganjuk and SMKN 1 Kertosono Nganjuk have similarities and differences. The equation is an affective domain of PAI learning evaluation reporting in the two schools together with the cooperation of PAI teachers, BK teachers and homeroom teachers. While the difference is that in SMAN 1 Kertosono Nganjuk the evaluation data is entered into the curriculum and then to the homeroom teacher and the BK then the curriculum is ready to print. Whereas at SMKN 1 Kertosono Nganjuk, each subject submitted the subject value to the evaluation section then submitted it to the homeroom teacher. Reporting the evaluation of PAI affective domain learning in SMAN 1 Kertosono Nganjuk and SMKN 1 Kertosono Nganjuk have similarities and differences. The equation is an affective domain of PAI learning evaluation reporting in the two schools together with the cooperation of PAI teachers, BK teachers and homeroom teachers. The difference is that in SMAN 1 Kertosono Nganjuk the evaluation data is entered into the curriculum and then to the homeroom teacher and the BK then the curriculum is ready to print. Whereas at SMKN 1 Kertosono Nganjuk, each subject submitted the subject value to the evaluation section then submitted it to the homeroom teacher.   Key Words: Affective domain evaluation,  PAI, Curriculum 2013.